Unilateral and Bilateral Strength Asymmetry among Young Elite Athletes of Various Sports - Kalata, Maros; Maly, Tomas; Hank, Mikulas; Michalek, Jakub; Bujnovsky, David; Kunzmann, Egon; Zahalka, Frantisek (Medicina (Kaunas, Lithuania), 2020)
Background and objective: Type of physical activity may influence morphological and muscular asymmetries in the young population. However, less is known about the size of this effect when comparing various sports. The aim of this study was to identify the degree of bilateral asymmetry (BA) and the level of unilateral ratio (UR) between isokinetic strength of knee extensors (KE) and flexors (KF) among athletes of three different types of predominant locomotion in various sports (symmetric, asymmetric and hybrid). Material and methods: The analyzed group consisted of young elite athletes (n = 50). The maximum peak muscle torque of the KE and KF in both the dominant (DL) and non-dominant (NL) lower limb during concentric muscle contraction at an angular velocity of 60°·s-1 was measured with an isokinetic dynamometer. Results: Data analysis showed a significant effect of the main factor (the type of sport) on the level of monitored variables (p = 0.004). The type of sport revealed a significant difference in the bilateral ratio (p = 0.01). The group of symmetric and hybrid sports achieved lower values (p = 0.01) of BA in their lower limb muscles than those who played asymmetric sports. The hybrid sports group achieved higher UR values (p = 0.01) in both lower limbs. Conclusions: The results indicate that sports with predominantly symmetrical, asymmetrical, and hybrid types of locomotion affected the size of the BA, as well as the UR between KE and KF in both legs in young athletes. We recommend paying attention to regular KE and KF strength diagnostics in young athletes and optimizing individual compensatory exercises if a higher ratio of strength asymmetry is discovered.
Keywords: youth; svalová síla; Torque; Sports; isokinetic peak torque; Humans; točivý moment; sportovci; maladaptation; soccer; lidé; sporty; lower limbs; Muscle Strength; Athletes; kosterní svaly; Knee; muscular symmetry; koleno; Muscle, Skeletal